Kajian Algoritma Fuzzy c-shell cluster Dalam Analisis Fuzzy Clustering Menggunakan Optimasi Pengganda Lagrange - Azwar Habibi (FKIP Universitas Islam Jember, 2014)
In the group analysis (cluster analysis), there are several methods that have been developed, new methods which are much in demand is fuzzy clustering, fuzzy clustering in its development has been developed in a number of methods (algorithms) one of which is a method of fuzzy c-shell cluster .One method for algorithm to optimize the fuzzy c-shell clusters by using lagrange multipliers by means mendiferensialisasi the meter is in the fuzzy c-shell algorithm clusters. The main problem in the fuzzy c-shell algorithm clusters that determine the optimal parameter of the existing algorithms on the fuzzy c-shell cluster. This paper examines the methods of fuzzy c-shell clusters using lagrange multipliers in mathematics. The results showed that using lagrange multipliers obtained optimizationparameters by minimizing the objective functionlagrange multiplier function obtained using the optimum conditions for the parameters uik , vi and ri as obtained in the above equation is: Keywords: cluster analysis, fuzzy clustering, fuzzy c-shell clusters, the lagrange multiplier.